Regretful Ruminations: Jacques Rivière’s L’Allemand: Souvenirs et réflexions d'un prisonnier de guerre - Arabella L Hobbs (Studies in 20th & 21st Century Literature, 2017)
This article examines Jacques Rivière’s post-war work L’Allemand: Souvenirs et réflexions d'un prisonnier de guerre (1918) ‘On German nature: memories and reflections of a prisoner-of-war,’ as a response to the conflicting nexus of Catholicism and French nationalism in the aftermath of the First World War. A damning account of the German race, L’Allemand exposes Rivière’s tussle with his wartime and post-war identities, most strikingly exhibited in his moral distancing from the text he was to eventually publish. In resuscitating Riviere’s now forgotten text, this article engages with the post-war reception of a work whose peculiar context bears witness to the liminal status of those detained in First World War prison camps caught between trench and captor nation, enmity and empathy.
Keywords: First World War; Prisoners; Franco-German relations; Regret